A Review of the Friction Stir Welding of Dissimilar Materials between Aluminum Alloys and Copper - Yumeng Sun; Wenbiao Gong; Jiacheng Feng; Guipeng Lu; Rui Zhu; Yupeng Li (Metals, 2022)
With the rapid development of various industries, the connection of copper and aluminum is in high demand. However, as a solid-phase connection technology, friction stir welding has a potential application prospect in the connection of copper and aluminum. This paper comprehensively summarizes the most recent 20 years of the literature related to the friction stir welding of copper and aluminum. The application significance of copper and aluminum connectors is introduced, and the research field of the friction stir welding of copper and aluminum is analyzed and explored from the aspects of welding technology, microstructure and mechanical properties, as well as innovations and improvements in the welding process. In view of the research status of this field, the authors put forward their views and prospects for its future, aiming to provide a basis for researchers in this field.